Association of early skin breaks and neonatal thalamic maturation: A modifiable risk?. (15th December 2020) - Duerden, Emma G.; Grunau, Ruth E.; Chau, Vann; Groenendaal, Floris; Guo, Ting; Chakravarty, M. Mallar; Benders, Manon; Wagenaar, Nienke; Eijsermans, Rian; Koopman, Corine; Synnes, Anne; Vries, Linda de; et al.
Abstract : Objective: To test the hypothesis that a strategy of prolonged arterial line (AL) and central venous line (CVL) use is associated with reduced neonatal invasive procedures and improved growth of the thalamus in extremely preterm neonates (<28 weeks' gestation). Methods: Two international cohorts of very preterm neonates (n = 143) with prolonged (≥14 days) or restricted (<14 days) use of AL/CVL were scanned serially with MRI. General linear models were used to determine the association between skin breaks and thalamic volumes, accounting for clinical confounders and site differences. Children were assessed at preschool age on standardized tests of motor and cognitive function. Outcome scores were assessed in relation to neonatal thalamic growth. Results: Prolonged AL/CVL use in neonates (n = 86) was associated with fewer skin breaks (median 34) during the hospital stay compared to restricted AL/CVL use (n = 57, median 91, 95% confidence interval [CI] 60.35–84.89). Neonates with prolonged AL/CVL use with fewer skin breaks had significantly larger thalamic volumes early in life compared to neonates with restricted line use (B = 121.8, p = 0.001, 95% CI 48.48–195.11). Neonatal thalamic growth predicted preschool-age cognitive (B = 0.001, 95% CI 0.0003–0.001, p = 0.002) and motor scores (B = 0.01, 95% CI 0.001–0.10, p = 0.02). Prolonged AL/CVL use was not associated with greater incidence of sepsis or multiple infections. Conclusions: Prolonged AL/CVL use in preterm neonates may provide an unprecedented opportunity to reduce invasive procedures in preterm neonates. Pain reduction in very preterm neonates is associated with optimal thalamic growth and neurodevelopment.